2009
DOI: 10.1093/ije/dyp195
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status and oesophageal cancer: results from a population-based case–control study in a high-risk area

Abstract: The strong association of SES with OSCC after adjustment for known risk factors implies the presence of yet unidentified risk factors that are correlated with our SES measures; identification of these factors could be the target of future studies. Our results also emphasize the importance of using multiple SES measures in epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 184 publications
(164 citation statements)
references
References 37 publications
9
154
1
Order By: Relevance
“…Systolic and diastolic blood pressures for each participant were also measured twice on both arms, with 10-minute intervals, in the sitting position. A wealth score was calculated as described in detail elsewhere (37). Briefly, to build a composite score for wealth, multiple correspondence analysis was used on the variables house ownership, house structure, house size, having a bath in the residence, and occupation, as well as possession of a personal automobile, a motorbike, a blackand-white television, a color television, a refrigerator, a freezer, a vacuum cleaner, and a washing machine.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Systolic and diastolic blood pressures for each participant were also measured twice on both arms, with 10-minute intervals, in the sitting position. A wealth score was calculated as described in detail elsewhere (37). Briefly, to build a composite score for wealth, multiple correspondence analysis was used on the variables house ownership, house structure, house size, having a bath in the residence, and occupation, as well as possession of a personal automobile, a motorbike, a blackand-white television, a color television, a refrigerator, a freezer, a vacuum cleaner, and a washing machine.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…17 This score had shown some association with ESCC risk in this population independent of education level. 11 These scores were categorized as quintiles according to the observed coordinates among control subjects.…”
Section: Discussionmentioning
confidence: 78%
“…They have concluded that the elements of social capitals including training social welfare, marriage, and socioeconomic status etc. has had a reverse and significant relation with the occurrence of this cancer [26,28].…”
Section: Discussionmentioning
confidence: 95%